Deep brain stimulation in the globus pallidus externa promotes sleep. (13th May 2016) - Qiu, M.H.; Chen, M.C.; Wu, J.; Nelson, D.; Lu, J.
Highlights: DBS in the GPe promotes natural sleep in rats. DBS in GPe activates endogenous sleep system. GPe is an intriguing candidate site for DBS to treat both insomnia and motor dysfunction. Abstract: The basal ganglia, a network of subcortical structures, play a critical role in movements, sleep and mental behavior. Basal ganglia disorders such as Parkinson's disease and Huntington's disease affect sleep. Deep brain stimulation (DBS) to treat motor symptoms in Parkinson's disease can ameliorate sleep disturbances. Our series of previous studies lead the hypothesis that dopamine, acting on D2 receptors on the striatopallidal terminals, enhances activity in the globus pallidus externa (GPe) and promotes sleep. Here, we tested if DBS in the GPe promotes sleep in rats. We found that unilateral DBS (180 Hz at 100 μA) in the GPe in rats significantly increased both non-rapid eye movement and rapid eye movement sleep compared to sham DBS stimulation. The EEG power spectrum of sleep induced by DBS was similar to that of the baseline sleep, and sleep latency was not affected by DBS. The GPe is potentially a better site for DBS to treat both insomnia and motor disorders caused by basal ganglia dysfunction.